Validation of the USAT (Universal Simple Aging Test) procedure to simulate the short and long-term aging of Brazilian asphalts - Carvalho, Talita de Souza (2025)
The aging of asphalt binders is an inherent phenomenon associated with production, field application, and the service life of pavements, directly impacting their performance. However, the simulation of this aging in laboratories, especially long-term aging, is still uncommon, mainly due to the high cost of the required equipment. In the Brazilian context, this situation is further aggravated by the fact that the current specification does not include rheological performance parameters or long-term aging requirements, which discourages laboratories from adopting more robust evaluation practices. This study aims to enable alternative, more accessible, and practical procedures for simulating binder aging in Brazilian laboratories, without the need for conventional equipment such as the Rolling Thin Film Oven Test (RTFOT) and the Pressure Aging Vessel (PAV). For short-term aging, the Short-Term Universal Simple Aging Test simplified (STUSAT) was evaluated, while for long-term aging, a modified version of the Long-Term Universal Simple Aging Test (LTUSAT) was studied, reducing the procedure time from 40 to 7 hours by applying a higher temperature. Eight asphalt binders were analyzed, and the residues aged using the alternative methods were compared to those aged using the traditional ones. The comparison was based on rheological parameters such as |G*|/ sin δ, upper continuous grade, Performance Grade (PG), Multiple Stress Creep Recovery (MSCR) outputs (including J and percent recovery %R at 3.2 kPa and J<sub<nr,dif ƒ) in addition to mass change for short-term aged residues. On the other hand, for long-term residues the rheological parameters evaluated were creep stiffness S(60), relaxation rate m-value, |G*|. sin δ, complex modulus |G*|, phase angle δ, Glover-Rowe parameter, R-value, and Δ. The results showed a strong correlation between the methods, indicating that both the STUSAT and the modified LTUSAT can reliably reproduce the effects of short- and long-term aging, respectively. Therefore, this study contributes significantly to the implementation of simpler, and more cost-effective protocols, supporting the development of a Brazilian specification based on the Performance Grade system.